2008
DOI: 10.1186/1477-7525-6-99
|View full text |Cite
|
Sign up to set email alerts
|

The responsiveness of the uterine fibroid symptom and health-related quality of life questionnaire (UFS-QOL)

Abstract: Background: A number of noninvasive alternatives to hysterectomy have become available as treatments for uterine fibroids. These alternative therapies, however, may not relieve all symptoms. Consequently, the need for patient-reported outcomes to assess symptom reduction of uterine fibroids has become increasingly important to evaluate the clinical success of patients who choose these alternative therapies. The purpose of the study was to examine the responsiveness of the Uterine Fibroid Symptom and Health-Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 26 publications
1
95
0
7
Order By: Relevance
“…Responsiveness to treatment was also evaluated in this study as an outcome measure to be considered as useful must demonstrate responsiveness to treatment effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Responsiveness to treatment was also evaluated in this study as an outcome measure to be considered as useful must demonstrate responsiveness to treatment effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…The score from the eight questions (Likert scale) on the symptom severity score was transformed to a 0-100 scale (16,17). In addition, because pain is a significant factor for patients with adenomyosis, we asked patients to grade their menstrual pain level using a visual analogue scale score ranging from 0-10 (6).…”
mentioning
confidence: 99%
“…9,10 Although the impact on PRO measures caused by change in symptoms versus symptom/condition status at time of assessment was not directly compared, there are data from treatment of allergic rhinitis indicating that symptom severity and nasal condition at time of evaluation are closely associated with asthma treatment satisfaction. 10,11 Analysis of the 23 specific benefits assessed in the PSTB questionnaire showed that the highest satisfaction scores were seen with benefits more directly related to the symptoms of OAB (urgency, frequency, and incontinence), and increased bladder control, freedom, predictability, and confidence; aspects that are not commonly assessed in clinical studies but are important to patients.…”
Section: Discussionmentioning
confidence: 97%